Experimental evaluation of the airflow behaviour in horizontal and vertical Open Joint Ventilated Facades using Stereo-PIV. (August 2017) - Sánchez, M.N.; Giancola, E.; Suárez, M.J.; Blanco, E.; Heras, M.R.
Abstract: This research focuses on the analysis of Open Joint Ventilated Facades with both vertical and horizontal apertures. The fluid-dynamic and thermal behaviour of this passive system is experimentally evaluated at the horizontal and vertical joints. The experimental study is performed considering no wind, and solar radiation corresponding to 4 × 10 8, 9 × 10 8 and 1 × 10 9 Rayleigh values. The experimental analysis of the fluid-dynamic behaviour in the facade is conducted through the set-up and optimization of a Stereo-PIV facility. The stereoscopic technique is based on particle image velocimetry in fluids, calculating three dimensional vector velocity fields along selected surfaces inside the ventilated air cavity. Based on the instantaneous measured field velocity it is possible to calculate other factors such as the average field velocity and the turbulence intensity, or to identify the main turbulence structures in the flow. The results indicate that the mean velocity and the turbulence quantities are enhanced by buoyancy. It has also been observed that the instabilities in the flow increase with the Ra numbers. The airflow rate through the facade joints has been calculated. Additionally, the air temperature inside the ventilated cavity as well as the surface temperature of the panels has been monitored and compared. Highlights: Ventilated facades reduce the summer thermal loads due to the solar radiation. An open joint ventilated facade model is designed and analysed. Stereo-PIV is used to measure the velocity field, and thermography for temperatures. Velocity and temperature values increase with Ra, maintaining the patterns. Complex flow structure with strong vortexes at the lower joints.